A remarkable new genus of Dikraneurini (Hemiptera: Cicadomorpha: Cicadellidae: Typhlocybinae) from Southeast Asia - Viraktamath, C. A.; Dietrich, C. H. (Zootaxa, 2011)
Sweta gen. n. is described and illustrated based on type species S. hallucinata sp. n. from northeast India and Thailand and placed in the typhlocybine tribe Dikraneurini. The new genus is unique among known Typhlocybinae in having the pronotum enlarged and extended to the scutellar suture. This feature is characteristic of the related subfamily Signoretiinae, but among other subfamilies is restricted to a few brachypterous forms.